The prevalence of tongue lesions in Malaysian dental outpatients from the Klang Valley area - Koay, C.L.; Lim, J.A.; Siar, C.H. (2011)
OBJECTIVES: To determine the prevalence of tongue lesions in Malaysian dental outpatients from the Klang Valley area. SUBJECTS AND METHODS: A cross sectional study was conducted on 600 Malaysian outpatients (257 men, 343 women, mean age, 37.7 years) attending the Primary Dental Care Unit at the Faculty of Dentistry, University of Malaya. Demographic and medical data were recorded for all respondents. RESULTS: One hundred eighty-one patients (30.2) (81 men, 100 women, mean age 42.0 years) were diagnosed with at least one tongue lesion (n = 207) at the time of examination. Of these, 24 patients (4) had two or more tongue lesions present synchronously. Seven different lesions were diagnosed: fissured tongue (13.8), crenated tongue (7.8), pigmented tongue (6.2), geographic tongue (2.2), ankyloglossia (1.7), hairy tongue (1.0) and median rhomboid glossitis (0.2). Their racial prevalences were Malays (n = 65, 10.8), Indians (n = 62, 10.3), Chinese (n = 53, 8.8) and other race (n = 1, 0.2). A significant relationship was observed between crenated tongue and race; between four types of tongue lesions (fissured tongue, geographic tongue, crenated tongue and pigmented tongue) and age; and between fissured tongue and gender (P < 0.05). CONCLUSIONS: Distribution characteristics of tongue lesions in Malaysians are important as local reference data in the daily clinical practice. Oral Diseases (2011) 17, 210-216